Molecular Dynamics (IntechOpen, 2018)
This book is devoted to a description of the modeling of nanosystems and a detailed exposition of the application of molecular dynamics methods to problems from various fields of technology: material science, the formation of composite molecular complexes, and transport of nanosystems. The research results of the modeling of various nanosystems are presented: soft supramolecular nanostructures, nanosized beams of single-crystal Cu, metallic nanosized crystals, drug delivery systems, and systems stabilized by hydrogen bonds. The information from this book will be useful for engineers, technologists, researchers, and postgraduate students interested in the study of the whole complex of computer simulation based on the concept of molecular dynamics methods for the task of designing and producing nanomaterials with controlled properties.